Real‐life data on basal cell carcinoma treatment: Insights on clinicians' therapeutic choices from an institutional hospital registry. Issue 6 (23rd October 2020) - Manoli, Sofia‐Magdalini; Moutsoudis, Andreas; Papageorgiou, Chryssoula; Lallas, Konstantinos; Rigas, Haris‐Marios; Kyrmanidou, Eirini; Papadimitriou, Ilias; Paschou, Eleni; Spyridis, Ioannis; Gkentsidi, Theodosia; Sotiriou, Elena; Vakirlis, Efstratios; et al.
Abstract: Basal cell carcinoma (BCC) is the most common skin cancer in white skin individuals. The treatment of choice is surgical excision, but several other therapeutic choices are available and might also be efficient and cost‐effective in selected cases of low‐risk BCC or when surgery is complicate or contraindicated. The aim of the current study was to analyze the applied treatments for BCC in the real‐life practice of a tertiary hospital, and investigate factors associated to the tumor and the patients that might influence the treatment selection of clinicians. Data on all BCCs treated from 1st January 2018 to 31st December 2019 were extracted. A total of 751 BCCs from 585 patients were included. The baseline characteristics of patients and tumors, the type of applied treatment and the histopathologic report when available were analyzed. Most tumors were located on the head/neck (64.2%). The most frequently applied treatment was surgical excision (580/751, 77.2%). In 22.8% of tumors a nonsurgical treatment was selected. The most frequently selected alternative treatments were, imiquimod, cryosurgery, their combination (immunocryosurgery), and vismodegib. A pretreatment diagnosis of superficial BCC was associated with a 12‐fold increased probability of selecting a nonsurgical treatment except of vismodegib. Every added year of age increased the probability of selecting a nonsurgical treatment by 3‐fold. Every added mm of diameter increased the possibility of vismodegib use by 4%. Surgery is the most frequently applied BCC treatment, but nonsurgical modalities do also have an essential role in real settings.